Platelet-rich plasma contains high levels of platelet-derived growth factor and transforming growth factor-beta and modulates the proliferation of periodontally related cells in vitro - Okuda, Kazuhiro; Kawase, Tomoyuki; Momose, Manabu; Murata, Masashi; Saito, Yoshinori; Suzuki, Hironobu; Wolff, Larry F; Yoshie, Hiromasa (Journal of periodontology (1970), 2003)
Platelet-rich plasma (PRP) is a fraction of plasma, in which platelet-derived growth factor (PDGF) and transforming growth factor-beta (TGF-beta) are thought to be concentrated. It is plausible that topically-applied PRP up-regulates cellular activity and subsequently promotes periodontal regeneration in vivo. However, the concentrations of these growth factors in PRP have not been specifically determined and the biological effects of PRP at the cellular and molecular levels have not been determined. PRP obtained from 20 healthy subjects was prepared from plasma by centrifugation. These PRP preparations were immediately subjected to an evaluation for PDGF-AB and TGF-beta1 using enzyme-linked immunosorbent assay (ELISA) kits. The biological effects of the PRP preparations were evaluated on osteoblastic, epithelial, fibroblastic, and periodontal ligament cells. Cellular mitogenic activity was evaluated by counting cell numbers or evaluating 5-bromodeoxyuridine (BrdU) incorporation. Expression of alkaline phosphatase (ALP) was immunocytochemically evaluated. In the PRP preparations, platelets were concentrated up to 70.9 x 10(4) cells/microl (283.4% of the unconcentrated plasma). The levels of PDGF-AB and TGF-beta1 were also concentrated up to 182.0 ng/ml (440.6%) and 140.9 ng/ml (346.6%), respectively. Scatter plots revealed significant correlations between platelet counts and levels of these growth factors. PRP stimulated osteoblastic DNA synthesis and cell division (138% of control), with simultaneous down-regulation of ALP, but suppressed epithelial cell division (80% of control). PRP also stimulated DNA synthesis in gingival fibroblasts and periodontal ligament cells. These data demonstrated that both PDGF-AB and TGF-beta1 were highly concentrated in the PRP preparations. It is suggested PRP modulates cell proliferation in a cell type-specific manner similar to what has been observed with TGF-beta1. Since synchronized behavior of related cell types is thought to be required for successful periodontal regeneration, it is further suggested these cell type-specific actions may be beneficial for periodontal regenerative therapy.